2013
DOI: 10.1111/ijcp.12103
|View full text |Cite|
|
Sign up to set email alerts
|

Dexrazoxane efficacy for anthracycline extravasation: use in UK clinical practice

Abstract: Extravasation is recognised as a major complication of administering intravenous chemotherapy treatment. Of the agents involved in extravasation, anthracyclines are associated with the greatest risk to patients because they are vesicant agents, having the potential to cause blistering and ulceration. If not identified and left untreated, anthracycline extravasation can lead to more serious complications such as tissue necrosis and functional impairment. Dexrazoxane (Savene(®) ) is the only licensed antidote fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2013
2013
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 22 publications
0
18
0
1
Order By: Relevance
“…As vesicants, anthracyclines are capable of inducing massive and long-lasting tissue injuries and blistering formations when extravasated [4,8]. Over several weeks, tissue destruction may progress and, in the worst case, severe necrosis and ulceration may eventually lead to an amputation [4,8,11].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…As vesicants, anthracyclines are capable of inducing massive and long-lasting tissue injuries and blistering formations when extravasated [4,8]. Over several weeks, tissue destruction may progress and, in the worst case, severe necrosis and ulceration may eventually lead to an amputation [4,8,11].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the pharmacological mechanisms of the bisdioxopiperazine dexrazoxane are not completely understood [7,11]. Several authors have suggested that due to the building of chelates as a metal ion chelator it may, firstly, prevent the formation of free radicals and, secondly, inhibit reversibly topomerase II, therefore working as a protective agent [1,3,7,8,10,11]. The recommended 3-day treatment schedule consists of a daily dose of 1,000 mg/m 2 on the 1st and 2nd days and 500 mg/m 2 on the 3rd day given once [1,2,4,5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations